Digital finance reduces urban carbon footprint pressure in 277 Chinese cities - Zheming Dong; Shujun Yao (Scientific Reports, 2024)
Abstract As global warming's impact on humanity surpasses initial predictions, numerous countries confront heightened risks associated with escalating urban carbon footprints. Concurrently, digital finance has flourished, propelled by advancements in digital technology. This convergence underscores the urgency of exploring digital finance's role in mitigating urban carbon footprint pressures. This study analyzes data spanning 277 Chinese cities from 2011 to 2020, yielding several key findings: Firstly, we developed a dataset detailing the carbon footprint pressures in these cities, revealing that variations in these pressures predominantly correlate with economic growth. Secondly, our analysis indicates that digital finance has a significant impact on reducing urban carbon footprint pressures, through mechanisms such as reducing the number of physical bank branches and enhancing residents' environmental awareness. Thirdly, the study identifies that the efficacy of digital finance in reducing carbon footprint pressures varies according to factors like sunshine duration and geographic location. The insights from this research aim to contribute substantively to strategies for sustainable urban development.